2007
DOI: 10.1007/s10577-007-1188-0
|View full text |Cite
|
Sign up to set email alerts
|

Possible autosomal origin of macro B chromosomes in two grasshopper species

Abstract: The acrocentric macro B chromosomes of Rhammatocerus brasiliensis (Acrididae, Gomphocerinae) and Xyleus discoideus angulatus (Romaleidae, Romaleinae) are highly similar to the X chromosome in each species in terms of morphology, size, and pycnosis. However, the results of FISH experiments using 45S and 5S rDNA probes suggest that in both species the B chromosomes are most likely of autosomal origin. In R. brasiliensis, the B chromosome presented 5S rDNA but not 45S rDNA, in resemblance to the L(2), L(3), M(5) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
48
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(59 citation statements)
references
References 27 publications
7
48
1
Order By: Relevance
“…This is because both 18S rDNA and H4 histone are present in the pericentromeric region of X and absent in B chromosomes. Additionally, C-banding and fluorochrome staining with CMA 3 /DA/DAPI showed different patterns of heterochromatic block distribution and composition among these chromosomes (Souza et al, 1998;Loreto et al, 2008). Rebollo et al (1998) suggested another hypothesis to explain the similarities between X and B chromosomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is because both 18S rDNA and H4 histone are present in the pericentromeric region of X and absent in B chromosomes. Additionally, C-banding and fluorochrome staining with CMA 3 /DA/DAPI showed different patterns of heterochromatic block distribution and composition among these chromosomes (Souza et al, 1998;Loreto et al, 2008). Rebollo et al (1998) suggested another hypothesis to explain the similarities between X and B chromosomes.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanisms, such as translocation and transposition, have been responsible for the dispersion of ribosomal sequences in the genomes and have been described for other grasshopper species Loreto et al, 2008). However, heteromorphism of the 18S rDNA is not uncommon in grasshoppers and variability in size, number, and location of sites has been described in several species (Souza and Moura, 2000;Cabral-de-Mello et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In insects, occur mainly in Diptera, Coleoptera and Orthoptera (Loreto et al, 2008). They may have different origins, including the derivation of autosomal (Jamilena et al, 1995), sexual chromosomes (LopezLeon et al, 1994) and resulting from interspecies crosses (Mcallister and Werren, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…This species has forty types of B variants along the populations found in the Mediterranean and Atlantic coasts of the Iberian Peninsula and North Africa (Cabrero et al, 1999). Loreto et al (2008) investigated the possible origin of macro B chromosome in Rhammatocerus brasiliensis and Xyleus discoideus angulatus populations originated in Northeastern region of Brazil. In these species, the B chromosome proved very similar to the X chromosome in morphology.…”
Section: Introductionmentioning
confidence: 99%